Digital Social Innovation: A new actor in the third sector? - Cannon, Sheila; Dart, Raymond (ARNOVA, 2019)
This exploratory paper examines a new and understudied phenomenon – the use of digital innovations to address social issues. While the influence and consequences of disruptive technology are the subjects of many articles, books and much speculation, very little has been written on the deliberate use of technology to engage social issues. Eight cases illustrate six different types of digital innovations that social entrepreneurs are using for social purposes. We situate our research within three areas of related literature: disruption and transformation caused by digital innovations; the use of technology in nonprofits and civil society initiatives; and social entrepreneurship and innovation. Findings highlight two types of Digital Social Innovations. Phase 1 consists of the Digital Start up, in which bright ideas from outside the field focus on pitching and presenting. Phase 2 is the Applied Innovation, where entrepreneurs faced resistance from the sector and experienced a steep learning curve. The significance of this research is to map out a new and ignored actor in the third sector: digital social innovations. We also contribute to understanding the process of how social entrepreneurs develop from innovative individuals to become more established social enterprises. We provide a definition of this term as well as some directions for future research.
ARNOVA (Association for Research on Nonprofit Organizations and Voluntary Action) 48th Annual Conference
Keywords: Social innovation; Social entrepeneur; Digital disruption; Creative Technologies; Digital Engagement; Inclusive Society; Social Enterprise & Social Entrepreneurship